2022
DOI: 10.1021/acs.chemmater.2c00689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stabilization of Cubic Gauche Polynitrogen under Radio-Frequency Plasma

Abstract: Cubic gauche polynitrogen (cgPN) has been very attractive because of its high energy density that is 3.5 times of the TNT energy. cgPN has been investigated theoretically in detail, but few experimental studies have been reported. In 2004, cgPN was first synthesized from nitrogen gas under extremely high temperature and high pressure conditions and the trace amount of cgPN in the high-pressure vessel decomposed once the pressure was released. Until recently, our group for the first time synthesized cgPN from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…In a follow-up detailed study in 2022 from the same group, Zhuang et al reported on a similar system. They explored both carbon nanotube-supported and unsupported NaN 3 , as well as N 8 – precursors . Vibrational spectroscopy again, combined with diffraction and density functional theory simulations, supported the claim of radiofrequency nitrogen plasma synthesis of the cubic gauche polymorph of polynitrogen at ambient pressure.…”
Section: Synthesismentioning
confidence: 89%
See 3 more Smart Citations
“…In a follow-up detailed study in 2022 from the same group, Zhuang et al reported on a similar system. They explored both carbon nanotube-supported and unsupported NaN 3 , as well as N 8 – precursors . Vibrational spectroscopy again, combined with diffraction and density functional theory simulations, supported the claim of radiofrequency nitrogen plasma synthesis of the cubic gauche polymorph of polynitrogen at ambient pressure.…”
Section: Synthesismentioning
confidence: 89%
“…The authors have presented some interesting electrochemical behavior of the materials. 34 The reported preliminary evidence suggests that there probably needs to be a condensed phase precursor involved in the synthesis of polynitrogen compounds by nonequilibrium plasma (Figure 6). This condensed phase is expected to serve two purposes: (1) it hosts the pentazolate compound, which is expected to be a condensed phase, mixed into a condensed phase, or on the surface of a condensed phase, and (2) it keeps the pentazolate temperature low to prevent thermal decomposition.…”
Section: Thementioning
confidence: 98%
See 2 more Smart Citations
“…For instance, the temperature and pressure requirements for diamond synthesis are as high as (30120 GPa, 1000–3000K) with shock waves, (15 GPa, 3000 -3500K) with HPHT, (5–10 GPa, 1500–2000K) with catalytic HPHT and (<1 GPa, <1500K) with plasma CVD 45 . The experimental work conducted in our group to synthesize the cubic gauche by plasma CVD is an example of the efforts within the scientific community to synthesize polymeric nitrogen compounds despite their metastability at ambient conditions 31 , 46 . Another key factor for a potential synthesis of a polynitrogen is a high energy lattice structure which has the capability of acquiring enough cohesive energy to overcome metastability.…”
Section: Introductionmentioning
confidence: 99%